Market composition anf performance of firms in broiler, chicken egg, and swine production implications to the Philippine Competition Act - Curibot, Janine P.; Elca, Cenon D.; Neric, Charis Mae T.; Gordoncillo, Prudenciano U. (2019)
The Philippine Competition Act promotes free and fair market competition to improve market efficiency and protect consumer welfare. Thus, it is necessary to examine and assess the nature of competition in any industry. This was done by conducting the study of broiler, chicken egg, and swine industries using the market structure-conductperformance approach. The degree of firm concentration, barriers to entry, profitability of production, return on investment, and share in every peso spent by the consumers were determined. Based on the analysis, markets for chicken egg and pork were fairly competitive while that of chicken meat was oligopolistic. Huge capital investment also showed to be a hindrance for greater competition in all the industries. Large share in consumer’s peso was more likely an issue in the chicken meat market than in chicken egg and swine. Monitoring the behavior of large firms, reducing structural barriers, and increasing production efficiencies are necessary to improve markets of these industries thus ensuring a vibrant competition.
Keywords: Market structure; Poultry industry; Agricultural marketing; Profitability